You don’t have to die : unraveling the AIDS myth - Chaitow, Leon (Puyallup (Washington): Future Medicine Publishing, Inc., 1994)
"Leon Chaitow, James Strohecker and the Burton Goldberg Group Fonds Suzan Daniel (FSD)"